ATIVIDADE PRÁTICA DE ESTRATÉGIAS COMERCIAIS: EVENTO ADM TÁ ON - Popp, Tadiane Regina; Mangolt, Daniel; Melo, Eduarda; Miguel, Gabrielli; Ribeiro, Jayne; Silva, Lucas (Anuário Pesquisa e Extensão Unoesc Joaçaba, 2022)
Este Resumo trata de uma atividade pratica de ensino